Cucurbituril-assisted formation of tunable carbon dots from single organic precursors in water. Issue 2 (16th October 2020) - Cao, Shixian; Wang, Pan; Zeng, Xi; Tao, Zhu; Ni, Xin-Long
Abstract : A facile method by utilizing the host–guest interaction of Q[ n ]s for the catalytic fabrication of CDs with high emitting qualities and a tunable particle size from a single organic precursor in water with high output has been demonstrated. Abstract : The cucurbit[7/8]uril (Q[7]/Q[8]) portal-based host–guest interaction was utilized to assist the formation of carbon dots (CDs) with a tunable particle size and high fluorescence emission via a hydrothermal reaction from a single organic precursor in water. In particular, the original rigid macrocyclic skeletons of these hosts were stably retained during the fabrication process, which helps in uniquely distinguishing them from other reported CDs. We obtained Q[7]-CDs with a long fluorescence lifetime (96 ns) and a high quantum yield (56.75%), and tunable fluorescence emission from the dynamic host–particle interaction of Q[8]-CDs, which can be further exploited as biosensors for 1-adamantanamine. This study showed that cucurbiturils have the unique advantage of generating CDs with high quality and new properties such as macrocycle-CD based host–gust chemistry.